Harmonic reduction in shunt active power filters with unusual energy sources (International Journal of Food and Nutritional Sciences, 2021)
The article discusses shunt active filter switching device control methods based on artificial neural network (ANN) theory. The fundamental goal is to minimize disturbances perfectly in both steady and transient states. A four-legged converter with a voltage source that can correct for biased currents and harmonic components brought on by non-linear loads is discussed in the study. Harmonic currents are reduced by using an active filter with a shunt connection. In contrast, the new suggested ANN controller for the reduction of % total harmonic distortion (THD). The foundation of the entire power filter idea is an ANN controller modelled in MATLAB. The potential of the system is illustrated by studying and simulating the suggested circuit in this research under various operating conditions.